Toll-like receptor 7/8 agonist resiquimod induces late preconditioning in neonatal cardiac myocytes - Wang Yong-yi; Liu Sha; Lian Feng; Yang Wen-gang; Xue Song (Acta Pharmacologica Sinica; Vol 32, No 5 (May 2011): Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether R-848 (resiquimod, toll-like receptor 7/8 agonist) can induce late preconditioning in neonatal cardiac myocytes. Methods: The protective effects of R-848 on neonatal myocytes against anoxia-reoxygenation-induced injury were tested, and intracellular reactive oxygen species (ROS) were determined. The protein synthesis inhibitor cyclohexamide (CH) and the ROS scavenger N-acetylcysteine (NAC) were used in this model to test if new protein synthesis and oxidative stress were necessary for their cardioprotective effects. The activation of nuclear factor kappa B (NFκB) and hypoxia inducible factor 1 (HIF1) was investigated by electrophoretic mobility shift assays (EMSA), and inducible nitric oxide synthase (iNOS) was assessed by immunoblotting. After iNOS was down-regulated by small interfering RNA (siRNA) transfection, the cardioprotective effect was reassessed. Results: ROS were triggered soon after R-848 (0.01–1.0 μg/L) administration, however, the cardioprotective effect of which was induced 24 h later. This protection was abolished by CH or NAC pretreatment. NFκB and HIF1 activation and iNOS up-regulation were involved in this protective mechanism. The cardioprotective effect was also attenuated after iNOS was knocked down. Conclusion: R-848 provided a cardioprotective effect through a late preconditioning mechanism via a ROS/NFκB-HIF1/iNOS-dependent pathway.